Transcriptomic exploration of a high sucrose mutant in comparison with the low sucrose mother genotype in sugarcane during sugar accumulating stage - Qaisar Khan; Jiao‐Yun Chen; Xu‐Peng Zeng; Ying Qin; Dao‐Jun Guo; Amir Mahmood; Li‐Tao Yang; Qiang Liang; Xiu‐Peng Song; Yong‐Xiu Xing; Yang‐Rui Li (GCB Bioenergy, 2021)
Abstract Sugarcane (Saccharum spp. hybrid) is a noteworthy crop in the world for sugar and bioenergy production. In the present study, transcriptomic analysis was steered for a high sucrose mutant Guixuan B9 (GXB9) and the low sucrose mother genotype B9 of sugarcane during sugar accumulating stage. A total of 112,170 unigenes were obtained, and 106,026 (94.52%) were annotated by using the available public databases nonredundant, Gene ontology, COG, Kyoto Encyclopedia of Genes and Genomes, Swiss‐Prot, and Pfam. Functional assignment analysis of unigenes exhibited that they were active in a diversity of metabolic pathways. The vital unigenes for sucrose metabolism and accumulation were relatively characterized in the immature internodes (int. 5, 6) and maturing internodes (int. 13, 14) of GXB9 in comparison with B9. The differentially expressed unigenes (DEGs) encoding sucrose phosphate synthase (SPS, EC2.4.1.14), sucrose synthase (SuSy, EC2.4.1.13), and invertase (EC3.2.1.26), which are the vital enzymes functioning in the biosynthesis and splitting of sucrose, in the internodal tissues were revealed by using Illumina Hiseq 2000 platform, and verified by quantitative reverse transcription‐polymerase chain reaction analysis. The DEGs encoding SPS proteins SPS1, SPS2, SPS4, and SPS5 were upregulated in the maturing internodes of GXB9 compared with B9. The DEGs encoding SuSy proteins were majorly upregulated in the immature internodes of GXB9, and those encoding the enzymes involved in trehalose synthesis were downregulated in GXB9 compared with B9. The results in this study have revealed the opportunities for future sugarcane improvement by concentrating on the DEGs linked to sucrose metabolic pathways by applying omics technologies.